Dobrowolne oszczędności emerytalne w Polsce - Wątorek, Bogumiła (Voluntary retirement savings in Poland, 2006)
The new pension system in Poland is composed of two elements: the obligatory part (I and II pillar) and the voluntary part (III pillar). According to the present projections, the pension received from the obligatory part will be too small to continue the standard of living achieved before retirement. That’s why it is very needed to save individually for the future pension. The main idea of this paper is to indicate and estimate the voluntary possibilities of saving money for the future retirement pensions, which are available in Poland. These are: employee pension programs, individual retirement accounts, investment funds, life insurance, real estate, bonds, shares, objects of art, etc. This article shows their advantages and disadvantages, but also their development in years 2000-2004.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 540-547